Analisis faktor human, organization, dan technology (hot-fit model) dalam penerapan peresepan elektronik (e-prescribing) - Agus Gede Made Artha; Ahdun Trigono; Yaya Aria Santosa (Holistik Jurnal Kesehatan, 2026)
Background: Digital transformation in the healthcare sector has encouraged hospitals to implement electronic prescription (e-prescribing) systems to improve service efficiency, minimize medication errors, and expedite medication management processes. However, the success of e-prescribing implementation depends not only on technological readiness but also on human factors and organizational support. The HOT-Fit model provides a comprehensive framework for evaluating the interaction between human, organizational, and technological factors in health information system implementation. Purpose: To analyze the influence of human, organizational, and technological factors (hot-fit model) on the implementation of electronic prescriptions (e-prescribing). Method: A mixed-methods design with a cross-sectional approach. Quantitative data were collected using questionnaires distributed to 47 physicians on duty (Physicians in Charge of Services) who actively use the e-prescribing system at the Outpatient Unit of Bhayangkara Hospital, Denpasar. Data were analyzed using multiple linear regression analysis. Results: Human factors had a positive and significant influence on satisfaction with electronic prescription implementation (β = 0.364; p = 0.006). Technological factors also had a positive and significant effect on satisfaction (β = 0.591; p = 0.000). Meanwhile, organizational factors did not show a significant effect on satisfaction (β = –0.222; p = 0.074). Together, human and technological factors contributed 68.8% (R² = 0.688; adjusted R² = 0.667) to the variation in satisfaction with e-prescription implementation. Conclusion: The success of e-prescription implementation is primarily influenced by human resource readiness and technology quality, while organizational factors did not show a significant effect on implementation satisfaction. Strengthening user capabilities and improving system quality are crucial to optimize the sustainability of e-prescription implementation. Suggestion: Hospitals should improve digital literacy among healthcare workers, ensure consistent implementation of standard operating procedures (SOPs), optimize e-prescription system features, and strengthen management commitment to create a more adaptive organizational environment that supports sustainable and user-oriented e-prescription implementation.   Keywords: Electronic Prescription; HOT-Fit Model; Human Factors; Organizational Factors; Technological Factors.